Pengaruh Pola Asuh Orang Tua dengan Perkembangan pada Balita Usia 1–3 Tahun di Desa Bangun Rejo Kabupaten Deli Serdang Provinsi Sumatera Utara Tahun 2024 - Nopalina Suyanti Damanik; Parningotan Simanjuntak; Plora Novita Febrina Sinaga; Ribur Sinaga; Maulidya Khairani; Isa Bella Simanjuntak (Universitas Muhamadiyah Manado, 2024)
Counseling with media can arouse and bring pregnant women into an atmosphere of joy and happiness, where there is emotional and mental involvement. The effectiveness of using counseling media is largely determined by the number of senses involved. The more senses used, the easier it is to understand the counseling message. This study aims to analyze the effect of counseling using audiovisual media on compliance with iron tablet consumption behavior in pregnant women in Bangun Rejo Village, Deli Serdang Regency, North Sumatra Province in 2024. This type of research is an intervention study using a true experimental research design. The design of this study is a pre-test and post-test with control group design. A pre-test was carried out, then an intervention was carried out on the experimental group and the control group, then a post-test was carried out on the experimental group and the control group with a time gap of two weeks. With a sample size of 32 pregnant women in the third trimester using the Wilcoxon test. The results showed an increase in compliance in the counseling group using audiovisual media was greater, namely 43.73 compared to the counseling group that did not use audiovisual media, namely 31.60. The data were then analyzed using an independent t-test with computer software and produced a p-value of 0.000 <0.05. Conclusion: Counseling using audiovisual media can increase compliance in consuming iron tablets compared to counseling alone without using media.